El derecho, la ciudad y el libre mercado en el Perú entre 1990-2023 - Calderón Cockburn, Julio (Pontificia Universidad Católica del Perú, 2025)
The article carries out a review of the laws issued in Peru between 1990 and 2023 that have effects on cities. Legislation from civil, urban, and environmental law is considered, affirming that the law is not uniform, but rather that within it, there are various orientations regarding private ownership of land, urban planning, informality, among other aspects. Based on a bibliographic review, the article concludes that there is a subordination of diffuse collective rights to private property rights, although changes are observed in this regard.

El artículo efectúa una revisión de las leyes expedidas en Perú entre 1990 y 2023 que tienen efectos sobre las ciudades. Se considera legislación del derecho civil, urbano y ambiental, afirmando que el derecho no es uniforme, sino que en su interior existen diversas orientaciones respecto a la propiedad privada del suelo, la planificación urbana, la informalidad, entre otros aspectos. Sobre la base de una revisión bibliográfica, el artículo concluye que existe una subordinación de los derechos colectivos difusos frente a los derechos de propiedad privada, aunque se observan cambios al respecto.
Law, the City, and the Free Market in Peru between 1990–2023
Keywords: State; Law; Private property; Urban Planning; Informality; Estado; Derecho; Propiedad Privada; Planificación Urbana; Informalidad; https://purl.org/pe-repo/ocde/ford#5.06.00